Concrete Subjected to Varying Confinement, I: Experimental Evaluation - Cetisli, Fatih; Naito, Clay J. (Japan Concrete Inst, 2009)
A study of the axial response of plain concrete under varying confining pressure was conducted to examine the sensitivity of confining pressure on the compressive strength and deformability of concrete. The concrete was examined through the use of a novel triaxial cell with pressure controlled through dilation strain feedback. The study examined realistic levels of constant, linear elastic, elastic-perfectly plastic, and bilinear varying confinement typical of fiber reinforced polymer and steel jacketing applications. It was found that the axial stress-strain response of confined concrete is dependent on the variation of confining pressure applied. The assumption of constant confinement is not appropriate for concrete systems jacketed with passive confinement such as steel or FRP materials. These systems must be comprehensively examined under varying confinement using full-scale jacketed specimens or triaxial studies. The use of a triaxial cell was shown to provide an efficient and cost-effective means of evaluating confinement performance.
Keywords: High-Strength Concrete; Triaxial Compression; Stress; Behavior; Model; Columns